Coexistence Of Vitiligo And Lichen Planus - Bhalla Mala; Sarkar Rashmi; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 2002)
The association of lichen planus with vitiligo is described in an Indian female patient and the possible underlying mechanisum responsible for their coexistence are discussed.